About hematology Peruvian wart - Monje, Carlos (1927)
Knowledge of haemopathy Peruvian wart or Carrion's disease, covering the complete study of a treaty of hematology. Indeed, in its severe forms hemático syndrome has a characteristic that does not fit in any other known. This syndrome worsen anemia making processes of its worst features and also has leukocyte alterations that make it comparable to certain leukemic processes